Association between the Oxytocin Receptor Gene Polymorphism (rs53576) and Bulimia Nervosa. (15th March 2015) - Kim, Youl‐Ri; Kim, Jeong‐Hyun; Kim, Chan‐Hyung; Shin, Jae Gook; Treasure, Janet
Abstract Objective Oxytocin circuits are implicated in the regulation of appetite and weight. Variants in the oxytocin receptor (OXTR) gene have been associated with bulimic behaviour. This study aimed to investigate the association between the OXTR gene and eating disorders. Method We genotyped six single nucleotide polymorphisms, rs53576, rs237879, rs2228485, rs13316193, rs2254298 and rs1042778, located within the OXTR gene in Korean patients with eating disorders using the single‐base extension method. We studied a total of 262 women, including 69 patients with anorexia nervosa, 90 patients with bulimia nervosa (BN), and 103 healthy women. Results We found a positive association between the G allele of OXTR rs53576 and BN. In the BN group, the G carriers showed a high score on the behavioural inhibition system. Conclusions These findings suggest the involvement of the oxytocinergic system in the mechanism that underlies BN. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.